Outcomes of gamma knife treated large symptomatic arteriovenous malformations according to guidelines of Taiwan neurosurgical consensus - Ming-Hsi Sun; Yuang-Seng Tsuei; Ting-Wei Wang; Szu-Yuan Liu; Ying Ju Chen; Chiung-Chyi Shen; Meng-Yin Yang; Jason Sheehan; Weir-Chiang You; Meei-Ling Sheu; Hung-Chuan Pan (Radiation Oncology)
Abstract Background The treatment of large arteriovenous malformations (AVMs), in particular those unruptured, remains a topic of debate. Stereotactic radiosurgery has favorable outcomes for small to medium-sized AVMs. However, for large AVMs, the goal is to maximize obliteration rates and at the same time, to minimize radiation-induced complications. This study assessed outcomes of large symptomatic AVMs treated with Gamma Knife radiosurgery (GKRS) focusing on cases presenting with rupture or seizures. The study followed the guidelines of Taiwan Neurosurgical Consensus, a government-funded committee under the Central Bureau of Health Insurance that determines whether radiosurgery is an appropriate treatment. Materials and methods This retrospective study included 75 cases of large AVMs (> 10 cc) treated with GKRS during the period from June 2003 to January 2020. Inclusion criteria were as follows: a history of intracerebral hemorrhage (ICH) or seizures, no prior embolization, and periodic MRI examinations with clinical assessments post-GKRS. Treatment procedures were adapted based on the Taiwan Neurosurgical Consensus guidelines. Results The average patient age was 36.4 ± 16.1 years, with a median follow-up duration of 104 (range 82–150) months. Forty-six patients (61.3%) underwent single-stage treatment, while 29 patients (38.7%) received two-stage treatment. The mean AVM volume was 20.5 ± 11.7 cc, with an average peripheral radiation dose of 17.7 ± 1.2 Gy. Among the 32 cases with AVM volumes between 10 and 15 cc, 25 (78.1%) achieved total obliteration. For the 17 cases with volumes between 15 and 20 cc, 7 (41.2%) achieved total obliteration, while 8 out of 26 (30.8%) cases with volumes > 20 cc achieved total obliteration. Severe brain edema developed in 16 patients (21.3%) after an average follow-up of 105.4 ± 56.2 months, but 11 patients (14.6%) experienced symptoms. Only one patient (1.3%) suffered neurological disability. Seizure control in Engel classification I was achieved in 21 of 42 patients (50%). Eight patients (10.6%) experienced new hemorrhages, with 4 (12.1%) occurring in those with a prior history of hemorrhage (annual bleeding rate: 1.2%) and 4 (9.5%) in those patients with a history of seizures (annual bleeding rate: 1.1%). Univariate analyses showed that total obliteration was significantly associated with smaller nidus volumes (< 15 cc), single-stage radiosurgery, Radiosurgery-Based Grading Scale, first-stage volume, maximum dose, 12 Gy volume, and nidus coverage percentages at 16 Gy and 18 Gy. Multivariate analyses revealed that post-GKRS symptoms and severe brain edema were significantly correlated with the following: Virginia Radiosurgery AVM Score, Charlson Comorbidity Index, and mean radiation dose. Conclusion The obliteration rate of large AVMs is strongly correlated with their size. This approach appears to achieve the goals of obliteration and minimizing the risks of radiation-induced complications and hemorrhage. Further investigation is needed for adjuvant treatments in residual or refractory cases after GKRS.